Racionamento de crédito, empreendedorismo e decisões ocupacionais - Raphael Castanheira Brandao (2012)
This dissertation investigates the existence of credit rationing in Brazil and their impact on entrepreneurship and occupational choice. Two kinds of occupational choice were studied to assess whether these choices were taken optimally or constrained by the presence of credit rationing. The first relates to how individuals choose to open a new business or to be an employee. The second choice evaluates the way a self-employed opts to dedicate exclusively to entrepreneurial activity or to have at the same time other jobs. The methodology employed in both cases was based on Evans & Jovanovic (1989), where it is indicated that personal wealth is relevant to an occupational choice if, and only if, there are failures in the credit market. Therefore, by investigating the relationship between personal wealth and occupational choices, this dissertation evaluates the existence of credit constraints in Brazil. The empirical analysis uses information from the Pesquisa de Orçamentos Familiares 2002/2003, a database still unexplored in studies related to credit market imperfections and occupational choice. The results suggest that the decision to start a new business is little influenced by credit constraints. But, the wealth was related to the search for multiple occupations among the self-employed, indicating that they are credit constrained. This is evidence that corrective actions on the supply of credit can have a major impact on the choices of management, operation and expansion of businesses already established.